Hak Asasi Manusia Bagi Masyarakat Yang Menolak Vaksinansi Covid-19 - Fernanda, Huzein Valdyan; Ferry Rosando, Abraham (Journal Evidence Of Law, 2023)
State law rule the people to obay the rules, specialy in Indonesia. As a state who take the community interests on the top, make the state do coercion for some rules for the people. In covid-19 pandemic situation is a hard time for the people because we had epidemic that threaten people's life, but the state give some protection by the obligation to get the covid-19 vaccination to protect the people by the epidemic so they can get normal activity. The law for must get covid-19 vaccinitation is enforced in many public activity so people must to have the covid-19 vaccinitation. Without law, people life did not in a good control, and the goverment want all the people get the best, so the goverment made the rule to supporting people’s good life so they can prottected from the virus in pandemic situation.the rule for people must had the vaccinitation belongs to all people, from the goverment, until the civilian, so they can protect eachother and didn’t get sick about covid-19 pandemic in the world, spescially in Indonesia.